Research Regarding a Correlation Core–Shell Morphology–Thermal Stability of Silica–Silver Nanoparticles. Issue 5 (3rd May 2016) - Postolache, Paraschiva; Petrescu, Valentin; Dumitrascu, Dan Dumitru; Rimbu, Cristina; Vrînceanu, Narcisa; Cipaian, Calin Remus
Abstract : Silica nanoparticles repeatedly inhaled lead to acute and chronic lung inflammation and finally to pulmonary fibrosis and lung cancer, people with chronic respiratory diseases like asthma or allergic rhinitis being even more susceptible to their toxic effects. In order to reduce these above-mentioned toxic effects, the aim of this study was to engineer the environmental silica nanoparticles with silver and subsequent thermal treatment. Nanometer-sized and spherical silica particles were synthesized in a homogeneous state, using a simple one-pot chemical method. An applicable approach resulted in silver particles forming over the surface of the silica. The outcome was materialized in extremely small silver particles attached to silica core particles. Playing their well-known decisive role, precursors and catalysts effectively controlled the size of silver and silica particles. The synchronized structure of the synthesized particles was revealed by the electrostatic repulsion among the silica spheres and the electrostatic attraction between silica spheres and silver particles. The morphological images are revealed by means of a scanning electron microscope. The formation of silver–silica composite particles was confirmed by using infrared spectroscopy and X-ray photoelectron spectroscopy analysis. Following thermal analysis, the results concerning the thermal stability of the prepared particles provided higher temperature applications.